A critical analysis on Shariah Compliance in Information System of Islamic Banking: Evidence from Malaysian Islamic Banking - Mohamad Subini Abdul Samat (Universiti Sains Islam Malaysia, 2024)
Thesis (M.A)-- Faculty of Economics and Management, Universiti Sains Islam Malaysia, 2017